2006
DOI: 10.1111/j.1574-6968.1997.tb12775.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the abilities of proteins from Bartonella bacilliformis and Bartonella henselae to deform red cell membranes and to bind to red cell ghost proteins

Abstract: Infections in humans by Bartonella bacilliformis, but not Bartonella henselae, are characterized by invasion of red cells. Supernatants of culture medium from B. bacilliformis and B. henselae each contain a protein which causes invagination of membranes of human red cells and formation of intracellular vacuoles. These two proteins are very similar in molecular mass, heat stability and mechanism of action. B. henselae does not bind to human red cells, but human red cell ghost membrane proteins were recognized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…Other studies focused on the interaction of B. bacilliformis with host proteins on erythrocyte membranes, although it is not clear which interaction partners might serve as receptors for adhesion and which ones might possibly be involved in the invasion process. A first report showed that the sets of erythrocyte proteins bound by B. bacilliformis and B. henselae are remarkably similar and clearly include actin and spectrin (201), while a second study provided solid evidence that B. bacilliformis interacts with the ␣ and ␤ subunits of spectrin, band 3 protein, glycophorin A, and monomeric as well as dimeric glycophorin B (63), thereby specifying the previous results. Binding of B. bacilliformis to glycophorin B from solubilized erythrocytes was considerably enhanced if these had been treated with trypsin or neuraminidase before, but chemical removal of the carbohydrate moieties from erythrocytes abolished binding to all proteins (63).…”
Section: Infection Of Erythrocytessupporting
confidence: 62%
See 3 more Smart Citations
“…Other studies focused on the interaction of B. bacilliformis with host proteins on erythrocyte membranes, although it is not clear which interaction partners might serve as receptors for adhesion and which ones might possibly be involved in the invasion process. A first report showed that the sets of erythrocyte proteins bound by B. bacilliformis and B. henselae are remarkably similar and clearly include actin and spectrin (201), while a second study provided solid evidence that B. bacilliformis interacts with the ␣ and ␤ subunits of spectrin, band 3 protein, glycophorin A, and monomeric as well as dimeric glycophorin B (63), thereby specifying the previous results. Binding of B. bacilliformis to glycophorin B from solubilized erythrocytes was considerably enhanced if these had been treated with trypsin or neuraminidase before, but chemical removal of the carbohydrate moieties from erythrocytes abolished binding to all proteins (63).…”
Section: Infection Of Erythrocytessupporting
confidence: 62%
“…It has been suggested that a secreted bacterial factor, deformin, would cause the membrane invaginations (440), but its molecular identity, mode of action, and secretion mechanism have remained elusive so far, although a well-documented phenomenology allows us to assemble a basic picture of its functionality. Importantly, deformation could also be demonstrated for B. henselae, making it likely to be a common feature of Bartonella erythrocyte infection (201).…”
Section: Infection Of Erythrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Although it is known that Bartonella species invade erythrocytes in their animal reservoir hosts, 13 there is no evidence for a direct interaction of B henselae with human erythrocytes. 14 An in vivo model with similarities to human trench fever has been described, in which rats were infected intravenously with B tribocorum leading to intraerythrocytic presence of bacteria during the course of infection. 4 Bacteria were first detectable in erythrocytes 5 days after challenge with a peak between 10 and 14 days after infection.…”
mentioning
confidence: 99%